Daring greatly : how the courage to be vulnerable transforms the way we live, love, parent and lead - Brown, Brené (New York Avery, 2012)
Every day people experience the uncertainty and emotional exposure that define what it means to be vulnerable. Here, Dr. Brown challenges everything people think they know about vulnerability, saying it is not weakness but rather the clearest path to courage and meaningful connection.
Keywords: Emociones; Asertividad (Psicología); Valor